Temperature and nutrient effects on the relative importance of brown and green pathways for stream ecosystem functioning: A mesocosm approach. (8th January 2020) - Gossiaux, Alice; Rollin, Marc; Guérold, François; Felten, Vincent; Laviale, Martin; Bachelet, Quentin; Poupin, Pascal; Chauvet, Eric; Bec, Alexandre; Danger, Michael
Abstract: In addition to global warming, aquatic ecosystems are currently facing multiple global changes among which include changes in nitrogen (N) loads. While several studies have investigated both temperature and N impacts on aquatic ecosystems independently, knowledge on their interactive effects remains scarce. In forested headwater streams, decomposition of leaf litter represents the main process ensuring the transfer of nutrients and energy to higher trophic levels, followed by autochthonous primary production, mainly ensured by phototrophic biofilms. The main aim of this study was to disentangle the independent and combined effects of temperature increase and nutrient availability on the relative importance of brown and green processes involved in stream functioning. We hypothesised that water temperature and nutrients would lead to a general increase in leaf‐litter decomposition and primary production, but that the intensity of these effects would be largely modulated by competitive interactions arising between microorganisms as well as by the top‐down control of microorganisms by macro‐invertebrates. Macro‐invertebrates would, in turn, be bottom‐up controlled by microbial resources quality. To test these hypotheses, we conducted a 56‐day experiment in artificial streams containing leaf litter, microbial decomposers and biofilm inoculum, and an assemblage of macro‐invertebrates. Two water inorganic N:phosphorus (P) ratios (33 and 100, molar ratios) and two temperatures (ambient, +2°C) were manipulated, each treatment being replicated three times. Fungal and biofilm growth as well as leaf‐litter decomposition and primary production were quantified. Top‐down impacts of invertebrate primary consumers on brown and green compartments were evaluated using exclosures while bottom‐up control was evaluated through the measurement of resource stoichiometry and fatty acid profiles, as well as quantification of macro‐invertebrate growth and survival. Contrary to expectations, microbial decomposition was not significantly stimulated by nutrient or temperature manipulations, while primary production was only improved under ambient temperature. In the + 2°C treatment with high N:P, greater biofilm biomass was associated with lower fungal development, which indicates competition for nutrients in these conditions. Temperature increased macro‐invertebrate growth and leaf‐litter consumption, but this effect was independent of any improvement of basal resource quality, suggesting that temperature mediated changes in consumer metabolism and activity was the main mechanism involved. Most of our hypotheses that were based on simplified laboratory observations have been rejected in our semi‐controlled mesocosms. Our study suggests that the complexity of biological communities might greatly affect the response of ecosystems to multiple stressors, and that interactions between organisms must be explicitly taken into account when investigating the impacts of global change on ecosystem functioning.